Relationship between G protein level with left ventricular systolic function in children with acyanotic heart disease - Dimiati, Herlina; Srikandi, Mira; Haypheng, Te; Sovira, Nora; Herdata, Heru N.; Bakhtiar, Bakhtiar; Edward, Eka D. (Narra J, 2024)
Heart failure is a pediatric emergency caused by the heart's inability to adequately meet the body metabolic needs and the most common cause is congenital heart disease (CHD). The G protein is the most prominent family of membrane-bound protein known to act in major regulatory events of the cardiovascular system, one of which is heart failure. The aim of this study was to determine the level of G protein and its relationship with left ventricular systolic function in children with acyanotic CHD. A cross-sectional study was conducted in Dr. Zaionel Abidin Hospital, Banda Aceh, Indonesia. The patients aged 0 to 18 years and had acyanotic CHD diagnosis by echocardiography were included. Anthropometry measurement was performed according to standard WHO procedures and G protein level was measured using the ELISA method. The Chi-squared test was used to measure the relationship between G protein level and left ventricular systolic function. Out of a total of 38 children with acyanotic CHD, the mean level of G protein was 36.25 ng/mL and the mean of left ventricular systolic function was 73.1%. There was no relationship between G protein and left ventricular systolic function in children with acyanotic CHD. However, further study with a larger sample size and considering other variables are needed to confirm this finding.